Firm Size and Price Book Value Impact on Stock Return: Evidence from the Indonesian Stock Exchange - Helia, Suhelmi; Putra, Elsanra Eka; Hidayati, Habibatul (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aimed to examine the effect of firm size and price book value on the stock returns companies listed on the Indonesia Stock Exchange 2015-2019 period. Number of sample 134 companies with five years of observations using purposive sampling techniques, the sample selected as 670 observations. This study uses secondary data form of financial statements along with stock prices obtained from the homepage of the Indonesia Stock Exchange. The analytical method used is the Panel Data Regression Analysis. The results of this study are the size of the company (firm size) has a significant negative effect and the price book value has a significant positive effect on the stock returns in companies listed on the Indonesia Stock Exchange during the 2015-2019 period.